THE IMPACT OF STATE INVESTMENT POLICY ON THE DEVELOPMENT OF HUMAN CAPITAL IN CONTEMPORARY CONDITIONS - USENKO, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article aims to examine the role of state investment policy in shaping human capital based on an analysis of its main directions, tools, and impact on social development. The article highlights the role of human capital as a key factor in economic growth, social progress, and national competitiveness. It emphasizes that a high level of human capital forms the foundation for sustainable societal development, ensuring adaptability to global challenges and changes. Particular attention is paid to the interconnection between state investment policy and the formation of human capital, which is a crucial aspect of ensuring economic progress. Public authorities must provide institutional support aimed at improving the levels of education, healthcare, and professional training of the population.The concept of state investment policy is explored as a component of the country’s economic policy, aimed at regulating investment processes across various economic sectors. The main investment directions are identified, targeting rapid economic development and improved quality of life, particularly in the field of human capital. The necessity of creating a favorable economic and legal environment for entrepreneurship and improving the investment climate is emphasized to attract investments in key social and economic sectors.The role of investments in enhancing labor productivity, promoting social mobility, reducing inequality, and fostering innovative development is outlined. The primary sources of investment in human capital are examined, including public spending, enterprise resources, household financing, and international support. The importance of efficient budget utilization and infrastructure development to support investments in human capital is underscored, including the adoption of new financing tools such as crowdfunding.Special attention is given to the issues of state investment policy under martial law, where the main tasks are attracting external financial assistance and optimizing the use of available resources to support human potential development. Directions for adapting investment tools to new challenges faced by the country are proposed.
Keywords: state investment policy; investment tools; human capital; investment sources; investment objects